2020
DOI: 10.21608/mjapfp.2020.171545
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adding Linseed or Sunflower Oils to Diets on the Performance of Broiler Chicks

Abstract: The present study was carried out in a private commercial broilers farm at Berket EL-Saab city, Menoufia governorate, Egypt, during the period from May to June 2019. The aim of this study was to investigate the impacts of adding two vegetable oils, linseed or sunflower, in broiler diets, on growth performance, some blood components, some carcass traits, immunity and economic efficiency. A total number of one hundred and eighty, one day old unsexed Arbor Acres broiler chicks were used in this study. Chicks were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
0
0
Order By: Relevance
“…The increase in the weight of the Fabricia also indicates an increase in the birds' ability to resist diseases and an increase in antibodies in the bird's body. These results were consistent with what was reported by [41] [42].…”
Section: Resultssupporting
confidence: 94%
“…The increase in the weight of the Fabricia also indicates an increase in the birds' ability to resist diseases and an increase in antibodies in the bird's body. These results were consistent with what was reported by [41] [42].…”
Section: Resultssupporting
confidence: 94%
“…These results agreed with many authors [17,18,19] who found that there is a significant increase in the weight of the living body when adding different percentages of animal fat in the diets of broilers either the results of weight gain showed the results of a significant superiority of the third and fourth treatments on the first treatment, which did not differ significantly from the second treatment and the reason for the superiority of the third and fourth treatment is that the addition of oils and fats (flaxseed oil and animal fat) led to improved palatability and increased the ratio digestive feed materials included in the diet and this is the reason for weight gain and this applies to what he reached [20,21] where they found that adding oils to broiler diets led to a significant increase in weights. These results were consistent with many researchers [15,22,23] who found a significant increase in weight gain when feeding broilers on different proportions of flaxseed oil and animal tallow, while the results of the consumed feed showed that there were no significant differences between the treatments and to explain this, it can be said that all the diets are close in their content of energy represented and therefore the feed consumption of these treatments and the extent of utilization of it will be almost the same. These results were consistent with some investigators [24,25] who found that there were no significant differences in feed consumption between the treatments when using different oil sources, including flaxseed oil and animal tallow, in broiler feed.…”
Section: Resultssupporting
confidence: 94%
“…This increase in body weight may be due to the presence of essential fatty acids in flax oil, especially the Linolenic Acid, which In turn, bile activates and leads to increased digestion of fat in the intestine, which leads to increased utilization of the diet [13]. These results are consistent with some authors [14,15] they observed a significant increase in living body weight when feeding broilers different percentages of flax oil. As for the increase in live body weight for animal tallow treatment, it may be due to the fact that animal tallow reduced the speed of food passing through the digestive system, allowing nutrients to be absorbed and used better [16].…”
Section: Resultssupporting
confidence: 90%